Bitter removal process optimization of soaked plum wine based on enzymatic hydrolysis and taste inhibition method - HAN Junran, WANG Fei, ZHAO Manxin, LI Yingtao, ZHENG Jingshao, HUANG Wei (Zhongguo niangzao, 2025)
Using soaked plum wine as the research object, the bitter was removed by amygdalin enzymatic hydrolysis method and β-cyclodextrin taste inhibition method. Taking removal rate of amygdalin as the evaluation index, two kinds of bitter removal processes were optimized by single factor tests and orthogonal tests. In addition, the correlation between amygdalin contents and bitter taste was discussed, and the color and odor of debitter soaked plum wine were determined by color difference instrument and electronic nose, respectively. The results showed that the optimal debittering process of amygdalin enzymatic hydrolysis method was as follows: amygdalinase addition 0.3 U/ml, enzymatic hydrolysis temperature 50 ℃, initial pH 4.8. The optimal debittering process of β-cyclodextrin taste inhibition method was as follows: β-cyclodextrin addition 1.0%, action temperature 40 ℃ and time 60 min. Under the optimal conditions, the removal rates of amygdalin in soaked plum wine were 25.54% and 23.92%, and the residues were 1.52 mg/L and 1.56 mg/L, respectively, which were lower than the threshold value (1.59 mg/L) in plum wine. The total color difference (ΔE value) of debitter wine sample with amygdalin enzymatic hydrolysis method and untreated wine sample was only 0.07, with less color difference. The typical fruit flavor substance benzaldehyde (methyl group) was well retained, the sulfur content was reduced, the sulfur odor was weakened, and the sensory quality of green plum wine was obviously improved. In conclusion, the two bitter removal processes could effectively reduce the bitter of soaked plum wine, and the amygdalin enzymatic hydrolysis method was better than β-cyclodextrin taste inhibition method.